Modified QuEChERS in blood sample preparation for drug abuse determination by LC-MS/MS - Boonchaleaw, Bundhita; Tansrisawad, Nat; Hoonwijit, Udomsak (Chulalongkorn Medical Journal, 2021)
Background: Liquid chromatography-tandem mass spectrometry (LC-MS/MS) becomes a common technique in the routine forensic toxicological analysis because of its accurate result. Solid-phase extraction (SPE) and liquid-liquid extraction (LLE) are the sample preparation methods having disadvantages from time-consuming and using a high quantity of harmful substances. Therefore, modified QuEChERS has been developed for routine toxicological laboratory for simpler sample preparation that could save time and decrease the use of toxic solvent for routine laboratory. Objective: To validate the modified QuEChERS technique for the blood sample preparation and to determine drug abuse in the blood sample using LC-MS/MS. Methods: Amphetamine, methadone, midazolam, morphine and triazolam were added to the blood. Modified QuEChERS was used for blood sample preparation and the analysis by LC-MS/MS was performed. Validation of the technique was tested and the application to the routine cases was done. Results: The chromatographic data of the interested abused drugs were obtained within 14 minutes. Modified QuEChERS extracted products could recover the 5 drugs in which the coefficient of determination of the calibration curves was higher than 0.99 and no influence of other drugs was found in the selectivity test. Conclusion: Modified QuECHERS is suitable for sample preparation before analysis with LC-MS/MS in routine forensic toxicology laboratory.